Alignment and Graphene‐Assisted Decoration of Lyotropic Chromonic Liquid Crystals Containing DNA Origami Nanostructures. Issue 12 (5th February 2016) - Martens, Kevin; Funck, Timon; Kempter, Susanne; Roller, Eva‐Maria; Liedl, Tim; Blaschke, Benno M.; Knecht, Peter; Garrido, José Antonio; Zhang, Bingru; Kitzerow, Heinz
Abstract : Composites of DNA origami nanostructures dispersed in a lyotropic chromonic liquid crystal are studied by polarizing optical microscopy. The homogeneous aqueous dispersions can be uniformly aligned by confinement between two glass substrates, either parallel to the substrates owing to uniaxial rubbing or perpendicular to the substrates using ozonized graphene layers. These opportunities of uniform alignment may pave the way for tailored anisometric plasmonic DNA nanostructures to photonic materials. In addition, a decorated texture with nonuniform orientation is observed on substrates coated with pristine graphene. When the water is allowed to evaporate slowly, microscopic crystal needles appear, which are aligned along the local orientation of the director. This decoration method can be used for studying the local orientational order and the defects in chromonic liquid crystals. Abstract : Liquid crystals may help to fabricate self‐assembled anisotropic photonic materials from tailored DNA origami nanostructures. First results show that films of respective nanocomposites can be uniformly aligned with their optical axis parallel or perpendicular to the substrate. In addition, a decoration phenomenon visualizing the liquid crystal director field is found to appear on graphene substrates.